(untitled) (World Bulletin of Management and Law, 2025)
This article analyzes the main characteristics and specific features of the document that affect the management of high-altitude ecosystems. Highaltitude areas have a complex structure, which requires a specific ecosystem management. The article focuses on the impact of the “Anthropogenic” factor, that is, the “Human” factor, which affects high-altitude ecosystems, that is, weakens them, ultimately bringing them to a completely irreversible level, and its specific features, using the example of the high-altitude areas of Andijan region (Uzbekistan), one of the most densely populated regions